1982
DOI: 10.1104/pp.70.2.528
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Benzyladenine by Tuber Slices of Jerusalem Artichoke (Helianthus tuberosus L.) over a Wide Concentration Range

Abstract: Uptake of the cytokinin benzyladenine by tuber slices of Jerusalem artichoke (HeImtks Obero L) Increased with the concentration of benzylademnle In the wndium in the range 10-' to 10-molar. The kinetics of uptake could be precisely represented by four phases of a single, multipbasic isotherm. K. and V.. increased in a regular manner upon transition to higher phases. The fit to multiphasic kinetics was significantly better than the fit to cooperative kinetics or to the sum of four Independent Michaels-Menten t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Disappearance of carbohydrate from the medium occurs rapidly -in suspension cultures of Rosa, the total carbohydrate of the medium (2% sucrose) disappeared by day 8-10 depending on the density of the inoculum [11]. The rate of BA uptake by Helianthus tuberosus cultures is very rapid and depends on BA concentration in the external medium [8], high concentrations promoting more rapid uptake than low concentrations. Thus, there would be considerable fluctuations in the level of these substances.…”
Section: Discussionmentioning
confidence: 98%
“…Disappearance of carbohydrate from the medium occurs rapidly -in suspension cultures of Rosa, the total carbohydrate of the medium (2% sucrose) disappeared by day 8-10 depending on the density of the inoculum [11]. The rate of BA uptake by Helianthus tuberosus cultures is very rapid and depends on BA concentration in the external medium [8], high concentrations promoting more rapid uptake than low concentrations. Thus, there would be considerable fluctuations in the level of these substances.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that BA is readily taken up by shoots from the medium (Minocha & Nissen, 1982;Nordstr6m & Eliasson 1986;Marino 1988). Agar influences the availability of cytokinins (Debergh 1983) and there exists an inverse correlation between uptake of 14C-labelled BA and agar concentration in the medium (Bornman & Vogelman 1984).…”
Section: Discussionmentioning
confidence: 99%
“…insets in Figs 1 and 3 in Shinkle and Briggs 1984), subsensitive dose responses of auxin can usually be represented by multiphasic isotherms with 2 or 3 phases, whenever sufficiently detailed and precise data are available.. These isotherms are, in principle at least, similar to those found for uptake of inorganic and organic solutes in plants (Nissen 1971, Minocha and Nissen 1982. Recently, evidence was obtained for uptake of 2,4-D and IAA into tuber slices of storage tissue via facilitated diffusion (Minocha and Nissen 1985).…”
Section: Discussionmentioning
confidence: 93%
“…In the case of wide dose response curves, improbably large chatiges in the concentration of PGS would be required for significant changes in their binding to the receptor (Trewavas 1981(Trewavas ,1982. In another development, uptake of benzyladenine by tuber slices of Jenisaletn artichokes was found to be precisely represented by a single, multiphasic isotherm (Minocha and Nissen 1982). As reported in a preliminary communication (Nissen 1983),, reanalysis of published dose response curves for PGS also yielded examples of multiphasic isotherms.…”
Section: Introductionmentioning
confidence: 83%